Valuations of Early-Stage Companies and Disruptive Technologies How to Value Life Science, Cybersecurity and ICT Start-ups, and their Technologies - Rothman, Tiran (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
XII, 219 p. 11 illus., 5 illus. in color.